2018
DOI: 10.1016/j.infsof.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The role and value of replication in empirical software engineering results

Abstract: Context: Concerns have been raised from many quarters regarding the reliability of empirical research findings and this includes software engineering. Replication has been proposed as an important means of increasing confidence. Objective: We aim to better understand the value of replication studies, the level of confirmation between replication and original studies, what confirmation means in a statistical sense and what factors modify this relationship. Method: We perform a systematic review to identify rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 64 publications
0
37
0
1
Order By: Relevance
“…They concluded that internal replications find confirmatory evidence eight times more than external replications. They also stressed the need to improve reporting on the original, replication and expected results [12].…”
Section: B Reviews Regarding Specific Aspects Of Replicationsmentioning
confidence: 99%
“…They concluded that internal replications find confirmatory evidence eight times more than external replications. They also stressed the need to improve reporting on the original, replication and expected results [12].…”
Section: B Reviews Regarding Specific Aspects Of Replicationsmentioning
confidence: 99%
“…As discussed by de Magalhaes et al [51] and Shepperd et al [71], one key issue related to replication in SE addresses the different procedures that can be followed to increase the chance of running a successful replication. Shepperd et al [71] highlight that this issue has been addressed by only a few studies and superficially. In a systematic mapping study that we conducted [68], we identified the techniques used to aggregate the results of groups of replications in SE: p-values, and more recently, effect sizes and their 95% confidence intervals (95% CIs), prediction intervals (95% PIs) and meta-analysis [79] [41].…”
Section: Related Workmentioning
confidence: 99%
“…Mature experimental disciplines, such as medicine, recommend the use of meta-analysis [33] [8] [78] [17] [7]. Some authors have also proposed its use in SE [71]. To the best of our knowledge, however, there has been no previous assessment in SE of how these approaches perform.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since, meta-analysis has been tightly coupled in SE with the concept of synthesizing the results of already published studies (i.e., typically with standardized effect sizes such as Cohen's d and AD) [3], [101], [129]- [131]. To do this, researchers should backcalculate appropriate effect sizes from study reports, and, if the studies are not very dissimilar, use either fixed-effects models or random-effects models for combination [3], [100], [101], [130].…”
Section: Related Workmentioning
confidence: 99%